2009
DOI: 10.1021/bm800691h
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Extruded Vital Wheat Gluten Sheets with Sodium Hydroxide and Salicylic Acid

Abstract: This paper presents a novel approach to improve the barrier and mechanical properties of extruded glycerol-plasticized vital wheat gluten sheets. The sheets were extruded with a single screw extruder at alkaline conditions using 3-5 wt % NaOH. Salicylic acid (SA), known to improve the extrudability of wheat gluten, was also added alone or in combination with NaOH. Oxygen transmission rate and volatile mass measurements, tensile tests, protein solubility, glycerol migration, infrared spectroscopy, and electroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
86
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 69 publications
(96 citation statements)
references
References 43 publications
8
86
2
Order By: Relevance
“…Protein polymerization properties have, in several studies, been shown to be the main determinant of tensile properties of gluten materials [5,13]. The present study gave very little evidence of any higher degree of polymerization of the rapeseed proteins in the rapeseed residuals used.…”
Section: Discussioncontrasting
confidence: 64%
See 3 more Smart Citations
“…Protein polymerization properties have, in several studies, been shown to be the main determinant of tensile properties of gluten materials [5,13]. The present study gave very little evidence of any higher degree of polymerization of the rapeseed proteins in the rapeseed residuals used.…”
Section: Discussioncontrasting
confidence: 64%
“…The most well known of those, being evaluated in a number of studies, is the wheat gluten, a residue from the starch/bioethanol industry and the protein-rich part from wheat after the starch and other carbohydrates have been washed away [11,12]. Gluten residue from the bioethanol industry has a high protein content (around 78%) and is possible to both compression mold and injection mold into materials of relatively high quality in terms of strength and barrier properties [5,13,14]. Examples of other plant proteins that have been reported to have potentials for materials production are soy and corn proteins [8,15,16].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…wheat gluten is high due to its high molar mass and aggregated structure. Nevertheless, it has been shown, by us and others, that plasticized wheat gluten can be compression molded and extruded into films, troughs and plates [3][4][5][6][7][8]. These methods, however, provide rather limited ways of shaping the material/product into more or less complicated three dimensional (3D) items.…”
Section: Introductionmentioning
confidence: 99%